ACMEOLOGICAL PECULARITIES OF TRAININGS OF FUTURE TEACHERS-PHILOLOGIST TO INTERCULTURAL COMMUNICATION - Markova, Tetiana V. (Educological discourse, 2015)
The article deals with the pecularities of training to cross-cultural communication in scientific literarture. The state of the researched problem is analyzed and the main general therms of intercultural communication and formation of readiness are analysed and are singled out in the philosophical, psychological and pedagogical literature.